A primer to the general theory of behavioral strategies in business-to-business marketing - Woodside, Arch (2014)
Copyright © 2014 by Emerald Group Publishing Limited.The general theory of behavioral strategies includes a set of propositions supporting alternative configurations of objectives, contextual features, and beliefs/assessments by executives. The theory includes the outcomes of selections of specific decision alternatives. Building behavioral-strategy models in contexts enriches one or more goals of science and practice: description, understanding, prediction, and influence/control. This chapter is a primer to the general theory. A brief review of relevant empirical studies supports the general theory. The empirical studies include the use of alternative data collection and analytically tools including true field experiments, think aloud methods, long interviews, statistical hypothesis testing, ethnographic decision tree modeling, and building and testing algorithms (e.g., qualitative comparative analysis, QCA). The general theory is the blending of cognitive science, economics, marketing, psychology, and implemented practices in explicit contexts. Consequently, behavioral-strategy theory is distinct from context-free microeconomics, market-driven, and competitor-only decision-making. Capturing and reporting contextually driven alternative routines to strategy setting by a compelling set of propositions represents what is particularly new and valuable about the general theory. The general theory serves as a useful foundation for advances theory and improving the practice of implemented strategies.